Biological and molecular characterization of seven Diaporthe species associated with kiwifruit shoot blight and leaf spot in China - DU, Yamin; WANG, Xianhong; GUO, Yashuang; XIAO, Feng; PENG, Yuhong; HONG, Ni; WANG, Guoping (Phytopathologia Mediterranea, 2021)
Diaporthe species are significant pathogens, saprobes, and endophytes, with comprehensive host association and geographic distribution. These fungi cause severe dieback, cankers, leaf spots, blights, and stem-end rot of fruits on different plant hosts. This study, explored the occurrence, diversity and pathogenicity of Diaporthe spp. associated with Actinidia chinensis and A. deliciosa in the main kiwifruit production areas of China. Diaporthe isolates (284) derived from 106 diseased leaf and branch samples were examined. Multi-locus phylogenetic analyses and morphology of 43 representative isolates revealed that seven Diaporthe species were obtained, including D. alangii, D. compactum, D. eres, D. hongkongensis, D. sojae, D. tectonae, and D. unshiuensis. Pathogenicity tests were performed on kiwifruit fruits, leaves and branches. Koch’s postulates confirmed all species were pathogenic. D. alangii and D. tectonae were the most aggressive species, followed by D. eres, D. sojae, D. hongkongensis, D. unshiuensis, and D. compactum. Host range evaluation showed that the seven Diaporthe species could also infect apricot, apple, peach, pear, and plum. This is the first report of D. alangii, D. compactum, D. sojae, D. tectonae, and D. unshiuensis infecting kiwifruit in China, increasing understanding of the Diaporthe complex causing diseases of kiwifruit plants, to assist effective disease management.